Patagonian Imaginary Nature: Colonial Narratives in Documentary Films on Subnational Spaces (1920–1955). - Zaidenwerg, Cielo; Dimant, Mauricio (Bulletin of Latin American Research, 2026)
This study contributes to the ongoing historical examination of ecological and postcolonial questions in Latin America through the lens of new media genre narratives. Early 20th‐century documentary films of Argentine Patagonia institutionalised a natural binary opposition, positioning those challenging colonial power relations based on natural resources against an ideal and achievable future. These narratives sought to shape dialogues and subjectivities about the region, defining the boundaries within which claims and changes were acknowledged. From this perspective, this research aims to advance the historical examination of the emergence of subnational future narratives and their connection with power dynamics in Latin America.